Incidence of acute volleyball injuries: a prospective cohort study of injury mechanisms and risk factors - Bahr, R.; Bahr, I. A. (Scandinavian Journal of Medicine & Science in Sports, 1997)
The purpose of the study was to examine the incidence and mechanisms of acute volleyball injuries, with particular reference to possible risk factors for ankle injuries. Coaches and players in the top two divisions of the Norwegian Volleyball Federation were asked to keep records of exposure time and all acute volleyball injuries causing a player to miss at least one playing day during one season. We found 89 injuries among 272 players during 51588 player hours, 45837 h of training and 5751 h of match play. The total injury incidence was 1.7 +/- 0.2 per 1000 h of play, 1.5 +/- 0.2 during training and 3.5 +/- 0.8 during match play. The ankle (54%) was the most commonly injured region, followed by the lower back (11%), knee (8%), shoulder (8%) and fingers (7%). Of the ankle injuries, 79% were recurrences, and the relative risk of injury was 3.8 (P < 0.0001) for previously injured ankles (38 of 232) vs. non-injured ankles (10 of the 234). Moreover, a reinjury was observed in 21 of the 50 ankles that had suffered an ankle sprain within the last 6 months (42.0 +/- 7.0%; risk ratio: 9.8 vs. uninjured ankles; P < 0.000001). The data indicate that external supports should be worn for 6-12 months after an ankle sprain and that specific injury prevention programs may be developed for ankle sprains in volleyball. Scand J Med Sci Sports 1997 Jun;7(3):166-71